EVALUASI IMPLEMENTASI KURIKULUM MERDEKA DI SMP NEGERI 4 SENTANI SEBAGAI SEKOLAH PENGGERAK - Resdianto, Andreas; Farida, Nurul; Sigalingging, Berlian Novalita; Destiyani, Gati; Ismanto, Bambang; Wasitohadi, Wasitohadi (Consilium: Education and Counseling Journal, 2025)
This study aims to determine the results of the Context, Input, Process, Product (CIPP) evaluation on the Evaluation of the Implementation of the Independent Curriculum at SMP Negeri 4 Sentani.This study is a mixed method (quantitative and qualitative) study that combines quantitative and qualitative methods. Participants in this study included lecturers, students, and the principal or head of administration at SMP Negeri 4 Senatni. One administrator, twenty-three educators, and one hundred and twenty-two students were all selected by purposive sampling based on their ability to provide the necessary data. Interviews, surveys, and documentation were the tools used in this study. Data reduction, data presentation, and drawing conclusions or verification were used to analyze qualitative data, while percentage techniques were used for quantitative data.The results of the study showed that the Evaluation of the Implementation of the Independent Curriculum at SMP Negeri 4 Sentani, the results were in the very good category. Each aspect of the evaluation consists of, (1) Context evaluation with a value of 3.67, using the implementation of KOSP in schools as a guideline for its implementation is very good, (2) Input evaluation with a value of 3.28, input evaluation consisting of eight indicators is very good in supporting the implementation of the independent learning curriculum (3) Process evaluation with a value of 3.32, consisting of learning planning, learning implementation, and learning evaluation is in accordance with the guidelines for implementing the independent learning curriculum used at SMPN 4 Sentani (4) Product evaluation with a value of 3.42, product evaluation must be carried out frequently in order to determine the development and progress of student learning outcomes and encourage learning motivation after completing the learning program. Based on the results of the study, it can be concluded that the evaluation of the implementation of the independent curriculum at SMPN 4 Sentani has been very good and effective in schools that have implemented the independent learning curriculum.